Fostering future music teachers' professional skills: developing a signature pedagogy using e-learning - Karkina, Svetlana; Mena, Juanjo; Valeeva, Roza; Yarmakeev, Iskander; Dyganova, Elena; Bhullar, Mandeep (Frontiers in Education, 2023)
Introduction The emergency crisis due to the COVID-19 pandemic caused noticeable changes that stimulated the transition to the new normal based on the digitalization of our systems. In this regard, the revision of learning tools in higher education exposes new challenges and requires the development and implementation of digital technologies. Fostering future music teachers' professional skills needs designing of online resources that provide close student–teacher interaction, as well as the engagement of students and regulation of their professional music practice. Based on the theory of Shulman, the signature pedagogy in music education was developed and implemented in an e-learning environment by a small private online course. The aim of the research was stated: How and which students' music teacher professional skills are affected in the process of e-learning based on the signature approach? The research was conducted at Kazan Federal University. During the educational process students studied the professional practicum. Methods Totally, 124 students from 1st to 4th academic level had taken part in the experimental work in the academic year 2021–2022. All of them studied bachelor programs for future music teacher as full- or part-time regime and studied the online course in MOODLE during the experiment. A combination of online tasks which cover all the types of the music teacher‘ professional activities was suggested. Considering the aim of the research, the multi-case study research methodology was chosen, using a mixed method approach, resourcing mainly to questionnaire, interview, documental analysis, and observation as data gathering methods, and descriptive statistical analysis, as data analysis techniques. Results The main results demonstrate the effectiveness of the developed online course that allowed to significantly foster students' music teacher professional skills. Discussion The investigation of the efficiency of using e-learning for training future music teachers' professional skills was carried out in this study. To improve future music teachers' skills according to the features of the professional field, a signature pedagogy approach was suggested. The contribution of the paper brings the detail characteristic of the signature pedagogy in music education, and the way of its implementation by the means of online tools.